Radical right : voters and parties in the electoral market - Norris, Pippa (Cambridge University Press, 2005)
This book expands our understanding of support for radical right parties through presenting an integrated new theory which is then tested systematically using a wealth of cross-national survey evidence covering almost forty countries, facilitating a broader perspective than ever before.